Pembuatan Media ‘Kartu Emosi Islami’ Untuk Membantu Regulasi Emosi Siswa Sekolah Dasar - Iqtianti, Haniefah; Anisak, Siti Darojatun; Mutiara, Yolanda (Yayasan Daarul Huda Kruengmane, 2025)
Improving emotional regulation skills in elementary school students is an essential need to support their social-emotional development and academic success. However, many students are still unable to identify, understand, and express their emotions appropriately. This community service activity aims to help elementary school students manage their emotions through the creation and use of “Islamic Emotion Cards.” This learning medium is designed by integrating Islamic values, illustrations of emotional expressions, and examples of behaviors aligned with religious teachings. The implementation method includes needs observation, card design, expert validation, and trials with students. The activities were carried out using an educational and participatory approach, giving students the opportunity to learn about different types of emotions, practice ways to manage them, and connect them with Islamic moral values. The results show that the “Islamic Emotion Cards” are effective in increasing students’ understanding of various emotions and encouraging them to express and control their emotions in more positive ways. Teachers also reported that the cards are easy to use in teaching and help create a more conducive classroom atmosphere. Thus, this medium can serve as an alternative educational solution for schools in developing students’ emotional regulation based on Islamic values.